Knowledge and Attitude of nurses regarding bioterrorism - Moshtagh- Eshgh, Z; Aghaei, N; Alavi Majd, H (Advances in Nursing & Midwifery, 2007)
Abstract Background: Modern biotechnology has enabled man to make benefit of microorganisms more efficiently than before but it is obvious that this powerful tool can be beneficial or dangerous to human beings depending on its use. Bioterrorism using biological weapons in terrorism is of great concern especially for healthcare workers as the first respondents to the victims. Purpose: This descriptive study was conducted to identify attitudes and knowledge of nurses concerning bioterrorism at hospitals affiliated to Mazandaran Medical University in Sari. Methods: 65 nurses were selected by non-probability sampling method. A questionnaire was used for collecting data. Content and Cronbach’s methods were used for validity and reliability of it. Results: Findings showed that 96.9% of the subjects had a very low knowledge concerning bioterrorism and 96.9% of them was also indifferent. Conclusion: Performing educational programs regarding bioterrorism is recommended because knowledge of nurses in this regard seems to be very low. Key words: Knowledge, Attitude, Bioterrorism, Nurses.